Komunikasi Persuasif dalam Kehumasan Digital: Studi Kasus Kelurahan Kerobokan Kaja - Ni Putu Risma Damayanti; Ni Putu Intan Permatasari (Universitas Islam Negeri Madura, 2025)
This study examines how Kelurahan Kerobokan Kaja builds its public image and connection with citizens through digital communication. Although social media is used to share public information, current practices remain predominantly one-way. The study aims to explain how persuasive communication is applied in the kelurahan’s digital public relations and how it contributes to shaping the local government’s image. A qualitative approach was employed through in-depth interviews, observation, and analysis of Instagram content. Thematic coding was used to identify forms of persuasion, message patterns, and government–public interaction dynamics. The findings show that informational content dominates, while persuasive elements and digital interaction remain limited. Message delivery relies heavily on peripheral cues such as visuals, but verbal messages rarely include dialogic invitations. Internal factors also constrain content variety and communication responsiveness. These conditions result in a digital image that is informative but not yet participatory or fully persuasive. The novelty of this study lies in its comprehensive mapping of how persuasion operates at the village administrative level through an in-depth analysis of local government digital PR practices. The study recommends strengthening the public relations role, diversifying content, and improving mechanisms for responsive digital dialogue.